2016
DOI: 10.4172/pharmaceutical-sciences.1000173
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Insulin, Leptin and Adiponectin Levels in Experimental Metabolic Syndrome Model by Some Drugs

Abstract: Al-Rasheed, et al.: Amelioration of Insulin, Leptin and AdiponectinA comparative study was planned to explore the modulating impact of metformin, Lipitor or orlistat against the metabolic syndrome components, including hyperglycemia and hyperlipidemia. Also, the effects of these drugs on leptin and adiponectin as biomarkers of metabolic syndrome in a rat model were investigated for the first time. The administration of these drugs each alone to metabolic syndrome induced rats markedly ameliorated the increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
2
0
0
Order By: Relevance
“…O n l i n e F i r s t O n l i n e F i r s t significantly reduced the increase in leptin levels, brought them to near-normal levels, and improved adiponectin levels. Our results are in agreement with previous research (Al-Rasheed et al, 2017;Stoica et al, 2021). Obesity is characterized by a wide range of circulating adipokine levels due to the aberrant accumulation and dysfunction of adipose tissues.…”
Section: Discussionsupporting
confidence: 94%
“…O n l i n e F i r s t O n l i n e F i r s t significantly reduced the increase in leptin levels, brought them to near-normal levels, and improved adiponectin levels. Our results are in agreement with previous research (Al-Rasheed et al, 2017;Stoica et al, 2021). Obesity is characterized by a wide range of circulating adipokine levels due to the aberrant accumulation and dysfunction of adipose tissues.…”
Section: Discussionsupporting
confidence: 94%
“…The results of this investigation showed that when compared to the controls, rats overfed with fructose resulted in elevated plasma glucose and insulin levels, increased insulin/glucose ratio, and decreased liver and muscle glycogen stores, confirming the report of AL-Rasheed et al (2016). Such changes may be associated with glucose tolerance and insulin resistance when there is an excess fructose supply.…”
Section: Discussionsupporting
confidence: 86%